PENGARUH KECERDASAN EMOSIONAL DAN MOTIVASI TERHADAP PRESTASI BELAJAR PADA SISWA KELAS V SDN 006 TERPADU KUBANG JAYA KAMPAR - Intan Permata Sari; Febrina Dafit (STKIP Subang, 2023)
This research was motivated by problems regarding student learning achievement. This research aims to determine whether there is an influence of emotional intelligence and learning motivation on the learning achievement of Class V students at SDN 006 Terpadu Kubang Jaya, Kampar Regency. This type of research uses a quantitative approach with an ex post facto research design. The population of this research is class V, totaling 32 students. Meanwhile, this research sample used a purposive sampling technique. Data collection techniques use questionnaires and documentation. Instrument testing uses validity and reliability. The data analysis technique uses descriptive analysis and prerequisite tests, namely normality test, linearity test, hypothesis testing in the form of multiple linear regression tests using the conditions Ha is accepted and H0 is rejected. Based on data processing research results, there is an influence of emotional intelligence and learning motivation on learning achievement of 43.9%.